Landscapes of Loss and Destruction : Sámi Elders' Childhood Memories of the Second World War - Koskinen-Koivisto, Eerika; Seitsonen, Oula (Open Library of Humanities, 2019)
The so-called Lapland War between Finland and Germany at the end of the Second World War led to a mass-scale destruction of Lapland. Both local Finnish residents and the indigenous Sámi groups lost their homes, and their livelihoods suffered in many ways. The narratives of these deeply traumatic experiences have long been neglected and suppressed in Finland and have been studied only recently by academics and acknowledged in public. In this text, we analyze the interviews with four elders of one Sámi village, Vuotso. We explore their memories, from a child’s perspective, scrutinizing the narration as a multilayered affective process that involves sensual and embodied dimensions of memory. peerReviewed